Explanation in typology Diachronic sources, functional motivations and the nature of the evidence - Schmidtke-Bode, Karsten; Levshina, Natalia; Michaelis, Susanne Maria; Seržant, Ilja (Language Science Press, 2019)
This volume provides an up-to-date discussion of a foundational issue that has recently taken centre stage in linguistic typology and which is relevant to the language sciences more generally: To what extent can cross-linguistic generalizations, i.e. statistical universals of linguistic structure, be explained by the diachronic sources of these structures? Everyone agrees that typological distributions are the result of complex histories, as "languages evolve into the variation states to which synchronic universals pertain" (Hawkins 1988). However, an increasingly popular line of argumentation holds that many, perhaps most, typological regularities are long-term reflections of their diachronic sources, rather than being 'target-driven' by overarching functional-adaptive motivations.